PENERAPAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT BERBANTUAN BAAMBOOZLE UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA SMK NEGERI 6 MEDAN - Yuliana Dewi Siregar; La Hanu; Andri Zainal; Ramdhansyah Ramdhansyah; Pasca Dwi Putra (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
The problem addressed in this study is the low level of students’ learning activity and learning outcomes in class XI AKL 1 at SMK Negeri 6 Medan. This condition indicates the need for the implementation of a learning model that can enhance students’ active involvement in the learning process. Although various studies have demonstrated the effectiveness of the Team Games Tournament (TGT) model and Baamboozle media in learning, their implementation to improve students’ learning activity and outcomes in Accounting for Service, Trading, and Manufacturing Companies at SMK Negeri 6 Medan remains limited. This study aims to improve students’ learning activity and outcomes through the implementation of the Team Games Tournament assisted by Baamboozle on the topic of adjusting entries in the Accounting for Service, Trading, and Manufacturing Companies subject for class XI AKL 1 at SMK Negeri 6 Medan. This study employed a Classroom Action Research (CAR) design conducted in two cycles using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages. The subjects of this study were 28 students of class XI AKL 1 at SMK Negeri 6 Medan in the 2025/2026 academic year. Data were collected through observation, tests, and documentation. Learning activity data were analyzed using student activity percentages, while learning outcome data were analyzed based on average scores and classical completeness. The results showed that the implementation of the Team Games Tournament model assisted by Baamboozle improved students’ learning activity and outcomes. Students’ learning activity increased, as indicated by the percentage of students categorized as active and highly active, which increased from 64.29% in cycle I to 96.43% in cycle II. Students’ learning outcomes also improved, with classical completeness increasing from 14.29% in the pre-test to 60.71% in the post-test of cycle I and further increasing to 100% in the post-test of cycle II. Therefore, the implementation of the Team Games Tournament model assisted by Baamboozle can improve students’ learning activity and outcomes in class XI AKL 1 at SMK Negeri 6 Medan. ABSTRAK Permasalahan dalam penelitian ini adalah rendahnya aktivitas dan hasil belajar siswa kelas XI AKL 1 SMK Negeri 6 Medan. Kondisi tersebut menunjukkan perlunya penerapan model pembelajaran yang mampu meningkatkan keterlibatan aktif siswa dalam proses pembelajaran.  Meskipun berbagai penelitian telah menunjukkan efektivitas model Team Games Tournament (TGT) dan media Baamboozle dalam pembelajaran, penerapannya untuk meningkatkan aktivitas dan hasil belajar siswa pada mata pelajaran Akuntansi Perusahaan Jasa, Dagang, dan Manufaktur di SMK Negeri 6 Medan masih terbatas. Penelitian ini bertujuan untuk meningkatkan aktivitas dan hasil belajar siswa melalui penerapan model Team Games Tournament berbantuan Baamboozle pada materi jurnal penyesuaian mata pelajaran Akuntansi Perusahaan Jasa, Dagang, dan Manufaktur di kelas XI AKL 1 SMK Negeri 6 Medan. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus dengan model Kemmis dan McTaggart yang meliputi tahap perencanaan, tindakan, observasi, dan refleksi. Subjek penelitian adalah 28 siswa kelas XI AKL 1 SMK Negeri 6 Medan Tahun Ajaran 2025/2026. Teknik pengumpulan data menggunakan observasi, tes, dan dokumentasi. Data aktivitas belajar dianalisis menggunakan persentase aktivitas siswa, sedangkan data hasil belajar dianalisis berdasarkan nilai rata-rata dan ketuntasan klasikal. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran Team Games Tournament berbantuan Baamboozle dapat meningkatkan aktivitas dan hasil belajar siswa. Hasil penelitian menunjukkan bahwa penerapan model Team Games Tournament berbantuan Baamboozle dapat meningkatkan aktivitas dan hasil belajar siswa. Aktivitas belajar siswa mengalami peningkatan, ditunjukkan dengan persentase siswa yang termasuk kategori aktif dan sangat aktif meningkat dari 64,29% pada siklus I menjadi 96,43% pada siklus II. Hasil belajar siswa juga menunjukkan peningkatan, dengan persentase ketuntasan klasikal yang meningkat dari 14,29% pada pretest menjadi 60,71% pada post-test siklus I dan meningkat kembali menjadi 100% pada post-test siklus II. Dengan demikian, penerapan model pembelajaran Team Games Tournament berbantuan Baamboozle terbukti dapat meningkatkan aktivitas dan hasil belajar siswa kelas XI AKL 1 SMK Negeri 6 Medan.